2021
DOI: 10.18844/ijntss.v5i2.5422
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the effects of Covid-19 on homelessness in Spain during the first quarantine

Abstract: This study aims to reflect the difficulties encountered by homeless people and homelessness in general, in the face of the crisis due to Covid-19, focusing on the situation in Spain. The paper describes the different responses carried out by different entities, both Spanish and international when dealing with homeless people. The study explains how the global solution of accommodation in different reception centres or hostels for homeless people, is not a solution that protects this group, but quite the opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The survivors reported minimization of social communications, losing friends, being unfriended on social media platforms, being verbally abused, and being called names (Dar et al, 2020). In the same study, Covid-19 survivors reported that they were being mocked by their communities, asked to vacate their houses by their landlords, denied access to private transport, and fired from their private jobs (Budian & Sarkute, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…The survivors reported minimization of social communications, losing friends, being unfriended on social media platforms, being verbally abused, and being called names (Dar et al, 2020). In the same study, Covid-19 survivors reported that they were being mocked by their communities, asked to vacate their houses by their landlords, denied access to private transport, and fired from their private jobs (Budian & Sarkute, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…As a result of the calculation, the reliability of the coding was found to be 94%. If the reliability calculation is over 70%, it is considered sufficient by the researchers for the research to be considered reliable [41,46]. Therefore, since the coding reliability of the data of this study is quite high, the codings are accepted as reliable.…”
mentioning
confidence: 99%